2004
DOI: 10.1111/j.1467-9396.2004.00447.x
|View full text |Cite
|
Sign up to set email alerts
|

Reform of European Merger Policy

Abstract: The paper highlights the main drivers for merger policy reform in the European Union, including the consequences of the recent appeal court reverses. It discusses some of the substantive and procedural issues that the reform package should address, and outlines the reforms in progress. The author concludes that much of the reform package will be beneficial, but some important opportunities have been missed in this inevitably patchwork process. Copyright Blackwell Publishing Ltd 2004.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 5 publications
0
18
1
Order By: Relevance
“…His work had an important role in the choice of a conditional acceptance in Phase I (Monti). 21 Unlike Bergman et al (2005), we found that his role as the head of the Antitrust Section undoubtedly affected merger decisions. Although his influence was largely stressed in the media, it was not found in previous empirical works.…”
Section: Model #1: Conditioning a Mergercontrasting
confidence: 52%
See 1 more Smart Citation
“…His work had an important role in the choice of a conditional acceptance in Phase I (Monti). 21 Unlike Bergman et al (2005), we found that his role as the head of the Antitrust Section undoubtedly affected merger decisions. Although his influence was largely stressed in the media, it was not found in previous empirical works.…”
Section: Model #1: Conditioning a Mergercontrasting
confidence: 52%
“…They all used a basic model to assess 6 Thus, the period covers the beginning of the new merger regulation passed in 2004. See, for instance, Lyons (2004) for further details about the procedure. 7 As Competition Commissioner for the EU Ms. Neelie Kroes says "Our aim is simple: to protect competition in the market as a means of enhancing consumer welfare and ensuring an efficient allocation of resources".…”
Section: Different Approaches To Assessing An Antitrust Authoritymentioning
confidence: 99%
“…This is commonly referred to as the dominance test (DT by US competition authorities. Some observers (e.g., Lyons, 2004) argue that the DT puts unnecessary weight on the concept of dominance in cases where the more important issue concerns the significant impediment of effective competition. The new merger regulation, which is applicable from May 1, 2004, focuses on a merger's impact on competition.…”
Section: Institutional Detailsmentioning
confidence: 99%
“…The determinants regressions for type I errors show similar coefficients estimates to the main specification, some of 32 Lyons (2004), for instance, notices that several changes in merger control were being implemented around 2003, such as the introduction of devil's advocate panels, the proposal of a clarification of the dominance test, the appointment of the first chief economist, the publishing of the draft merger guidelines and the extension for timetable for remedies.…”
Section: The Timing Of the Reformmentioning
confidence: 58%